2022
DOI: 10.1111/jog.15163
|View full text |Cite
|
Sign up to set email alerts
|

ITGA7, CD133, ALDH1 are inter‐correlated, and linked with poor differentiation, lymph node metastasis as well as worse survival in surgical cervical cancer

Abstract: Aim Integrin alpha 7 (ITGA7) regulates cancer stemness and metastasis in several malignancies, while its role in cervical cancer is obscure. Therefore, the current study aimed to investigate the correlation among ITGA7, cluster of differentiation 133 (CD133), and aldehyde dehydrogenase isoform 1 (ALDH1), as well as their relation to tumor features and survival in cervical cancer patients. Methods A total of 133 surgical cervical cancer patients were enrolled. Tumor ITGA7, CD133, and ALDH1 expressions were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(143 reference statements)
1
0
0
Order By: Relevance
“…Joseph et al showed that CD133 was significantly associated with poor prognostic characteristics in breast cancer patients, such as high histological grade, younger age, high Nottingham Prognostic Index, and estrogen and progesterone receptor negative subtypes that often are chemoresistant [177]. A similar observation was found for different cancers, such as gastric [28], colon [105], cervical [229], ovarian [108], and glioblastoma [230]. Therefore, CD133 as a molecular target is still an important "player" in targeted therapy.…”
Section: Limitations and Advantagesmentioning
confidence: 82%
“…Joseph et al showed that CD133 was significantly associated with poor prognostic characteristics in breast cancer patients, such as high histological grade, younger age, high Nottingham Prognostic Index, and estrogen and progesterone receptor negative subtypes that often are chemoresistant [177]. A similar observation was found for different cancers, such as gastric [28], colon [105], cervical [229], ovarian [108], and glioblastoma [230]. Therefore, CD133 as a molecular target is still an important "player" in targeted therapy.…”
Section: Limitations and Advantagesmentioning
confidence: 82%
“…Studies have found that solid tumors, including colorectal cancer (Chen et al, 2015), breast cancer (Pan et al, 2015), cervical cancer (Yuan et al, 2022), liver cancer (Yang et al, 2017), and ovarian cancer (Kim et al, 2017). ALDH1 plays a role in promoting carcinogenesis in breast cancer.…”
Section: The Roles Of the Aldh1 Family In Cancer Development And Prog...mentioning
confidence: 99%